2016
DOI: 10.1039/c6md00431h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro evaluation of the antitumor potential and chemo-sensitizing activity of fluorinated ecdysteroid derivatives

Abstract: Efflux pumps, like the ABCB1 transporter, play an important role in the chemo-resistance of various tumors and particularly of cancer stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…Ecdysteroids have a broad range of bioactivities in mammals, as extensively reviewed elsewhere [ 1 , 2 , 3 ]. In addition to these, it has recently been revealed that less polar derivatives of these compounds can exert a potent chemo-sensitizing activity in various multi-drug resistant [ 4 , 5 , 6 , 7 ] as well as drug susceptible [ 6 , 7 , 8 ] cancer cell lines. In particular, ecdysteroid dioxolanes such as 20-hydroxyecdysone 2,3;20,22-diacetonide were found by our group to effectively potentiate the in vitro antitumor activity of several chemotherapeutic agents including doxorubicin, paclitaxel, and vincristine, which was, however, not the case for cisplatin [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecdysteroids have a broad range of bioactivities in mammals, as extensively reviewed elsewhere [ 1 , 2 , 3 ]. In addition to these, it has recently been revealed that less polar derivatives of these compounds can exert a potent chemo-sensitizing activity in various multi-drug resistant [ 4 , 5 , 6 , 7 ] as well as drug susceptible [ 6 , 7 , 8 ] cancer cell lines. In particular, ecdysteroid dioxolanes such as 20-hydroxyecdysone 2,3;20,22-diacetonide were found by our group to effectively potentiate the in vitro antitumor activity of several chemotherapeutic agents including doxorubicin, paclitaxel, and vincristine, which was, however, not the case for cisplatin [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ecdysteroid dioxolanes such as 20-hydroxyecdysone 2,3;20,22-diacetonide were found by our group to effectively potentiate the in vitro antitumor activity of several chemotherapeutic agents including doxorubicin, paclitaxel, and vincristine, which was, however, not the case for cisplatin [ 6 ]. The strong synergistic action of certain ecdysteroids with one or more of the above-mentioned chemotherapeutics was confirmed on a broad range of cancer cell lines of various origin, including human breast (MCF-7 and its sub-cell line MCF-7 Dox adapted to doxorubicin), prostate (PC3, LNCaP), epidermal (KB-3-1 and its sub-cell line KB-C-1 adapted to colchicine), and neuroblastoma (SH-SY5Y), as well as two murine lymphoma cell lines (L5178 and its sub-cell line L5178 MDR transfected to express the human ABCB1 transporter, commonly referred to as P-glycoprotein or P-gp) [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the ecdysteroid analogs displayed moderate activities against the tested cell lines, the i-butyl substituted compound 10 was stronger than the positive control cisplatin on the HeLa and MDA-MB-231 cell lines. In our previous study, the antiproliferative IC 50 values of compound 1 were 106.1 and 75.1 µM on the MDA-MB-231 and MCF7 cell lines, respectively, [21] showing that the inclusion of certain oxime ether functions can increase this activity by nearly an order of magnitude. While the orientation of the oxime ether had no obvious effect on the activity, a larger alkyl group led to a stronger antiproliferative action.…”
Section: Accepted Manuscriptmentioning
confidence: 84%
“…[20] Regarding semi-synthetic modifications accompanied by the inclusion of heteroatoms, a difluorinated derivative of 20E 2,3;20,22-diacetonide was found to be a stronger P-gp inhibitor than its parental molecule (compound 1), while, surprisingly, MDR selectivity of the difluorinated compound was lower: it sensitized a P-gp expressing MDR cell line to doxorubicin similarly to its parental compound 1, and a stronger effect than that of 1 was observed on a non-MDR cell line. [21] The chemical structures of 20E and compound 1 are shown in Figure 1. Galyautdinov et al have previously reported the successful preparation of several (E/Z)-isomeric ecdysteroid 6-oxime and some lactam derivatives.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation